A New Look at Bronchopulmonary Dysplasia: Postcapillary Pathophysiology and Cardiac Dysfunction. (December 2016) - Sehgal, Arvind; Malikiwi, Andra; Paul, Eldho; Tan, Kenneth; Menahem, Samuel
Pulmonary hypertension (PH) and right ventricular function are the focus of cardiovascular effects of bronchopulmonary dysplasia (BPD). We assessed cardiac indexes reflecting systemic afterload and pulmonary venous back pressure as pathophysiologic factors. Cardiac parameters were measured by conventional echocardiography in 20 preterm infants with severe BPD and compared with those of 10 preterm infants with no BPD and 20 healthy term infants. In infants with severe BPD, PH was noted in 5 (25%) by tricuspid regurgitation Doppler jet ≥2.8 m/s and in 15 (75%) by time to peak velocity/right ventricular ejection time <0.34. Among systemic cardiac indexes, significant impairment of diastolic measures was noted in the BPD group compared with infants with no BPD and term infants. The significance persisted after adjusting for gestational age and birth weight. These included transmitral E/A ratio (1.07 ± 0.07 vs. 0.91 ± 0.04 vs. 0.89 ± 0.09; P < 0.0001), isovolumic relaxation time (68.8 ± 3.9 vs. 58.5 ± 7.8 vs. 54.2 ± 5.7 ms; P < 0.0001), mitral valve stroke volume (4.7 ± 0.7 vs. 5.6 ± 0.6 vs. 5.9 ± 0.1; P = 0.002), and myocardial performance index (0.33 ± 0.05 vs. 0.28 ± 0.01 vs. 0.27 ± 0.05; P = 0.03). Left ventricular output was significantly lower in the BPD cohort (183 ± 45 vs. 189 ± 9 vs. 191 ± 32 mL/kg/min; P = 0.03). Altered systemic (left-sided) cardiac function was noted in infants with BPD, which may lead to pulmonary venous congestion contributing to a continued need for respiratory support.